RNA N6-Methyladenosine and the Regulation of RNA Localization and Function in the Brain. Issue 12 (December 2020) - Madugalle, Sachithrani U.; Meyer, Kate; Wang, Dan Ohtan; Bredy, Timothy W.
Abstract : A major challenge in neurobiology in the 21st century is to understand how the brain adapts with experience. Activity-dependent gene expression is integral to the synaptic plasticity underlying learning and memory; however, this process cannot be explained by a simple linear trajectory of transcription to translation within a specific neuronal population. Many other regulatory mechanisms can influence RNA metabolism and the capacity of neurons to adapt. In particular, the RNA modification N 6 -methyladenosine (m 6 A) has recently been shown to regulate RNA processing through alternative splicing, RNA stability, and translation. Here, we discuss the emerging idea that m 6 A could also coordinate the transport, localization, and local translation of key mRNAs in learning and memory and expand on the notion of dynamic functional RNA states in the brain. Highlights: Epitranscriptomics or 'RNA modifications' contribute to RNA localization processes in the brain. N 6 -methyladenosine (m 6 A) is an RNA modification potentially critical for the localization of RNA. m 6 A not only has roles in the nuclear processing and export of RNA molecules but is also likely to contribute to the phase separation of RNA–protein complexes into RNA reservoirs [e.g., RNA granules, stress granules, processing (P)-bodies] and local translation at specific neuronal compartments. Many new techniques are capable of profiling m 6 A-modified transcripts at single-base resolution. However, these techniques need to be adapted to determine transcripts localized to various locations of the neuron including activated synapses, axons, and dendritic compartments. Investigations into the roles of m 6 A in RNA biology are rapidly expanding but require new techniques to fully understand m 6 A's role in RNA localization in the brain.